(الإرهاب الدولي والأمن الفكري والروحي ودولة ما بعد الاستعمار: دراسة في نظام القيم في القرآن (القسم الأول (Global Terrorism, Spiritual-Intellectual Security and the Post-Colonial State: A Study on the Qur’anic Valuational System (Part: 1)) - زين إبراهيم محمد (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
الملخّص يهدف هذا البحث لبيان أن السبيل الناجح لمواجهة الإرهاب الدولي المعاصر الملتبس بدعاوي الجهاد الإسلامي وإحياء دولة الخلافة الإسلامية هو التركز على معاني الأمن الفكري والروحي في الإسلام وهذا الاتجاه في المباحثة يُعيد النظر في طرائق قضايا الجهاد ويميز بين ما هو عقائدي ومرتبط بنظام الإسلام الكلي وبين ما هو من مجال حروب الفتنة والصعلكة. الكلمات المفتاحيّة: الجهاد، حروب الصعلكة، حروب الفتنة، الأمن الروحي والفكري. Abstract This study focuses on the most effective way of combating global terrorism that utilizes the banner of Jihad and restoration of the Khilafa system of governance. It should be emphasized that there is a dire need for a new line of investigation concerning the issue of Jihad that pays more attention to both spiritual and intellectual security systems in Islam. This requires a distinction to be made between what is universalistic in the Islamic system and what is particular. In this regard one has to differentiate between acts of just war and those of economic or sedition wars. Keywords: Jihad, economic war, sedition war, spiritual-intellectual security system.